2012
DOI: 10.1159/000336156
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan-Induced Dysarthria

Abstract: Colorectal carcinomas are among the most common tumor types and are generally treated with palliative chemotherapy in case of metastatic disease. Here, we describe the case of a 46-year-old patient with metastatic rectal carcinoma who received second-line therapy with irinotecan and developed isolated transient dysarthria (with normal MR imaging of the brain) following each administration of irinotecan. Neurological and logopedical evaluation revealed that the dysarthria predominantly resulted from a reduced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Furthermore, in this case the event was fully reversible and does not justify the discontinuation of the drug [15]. The duration of the event may vary between 15 min [16] and 24 h [17], but in most reported cases there was spontaneous resolution of the symptom after a few hours [11,14].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Furthermore, in this case the event was fully reversible and does not justify the discontinuation of the drug [15]. The duration of the event may vary between 15 min [16] and 24 h [17], but in most reported cases there was spontaneous resolution of the symptom after a few hours [11,14].…”
Section: Discussionmentioning
confidence: 86%
“…Only Gomez et al [9] reported a case of a patient who presented dysarthria associated to ataxia and tremors with complete resolution of the symptoms after administering atropine [9]. In this case dysarthria was not an isolated symptom, and the dose used was relatively lower to those administered in other case reports (80 mg/m²-350 mg/m²) [9,[14][15].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, the unexpectedly high incidence of dysarthria appears to be a characteristic adverse effect of FOLFIRINOX that extends beyond ethnicity. Conversely, it is known that irinotecan directly causes dysarthria, although only 10 cases have been reported in the literature (2,3,(6)(7)(8)(9)(10)(11)(12)(13). Although irinotecan exerts its antitumor activity after being metabolized to SN-38 in vivo, dysarthria is apparently caused by the parent compound irinotecan binding to the active site of Table I.…”
Section: Discussionmentioning
confidence: 99%